ERA EDUKASI 4.0 YANG BERBASIS KINERJA GURU BAHASA PADA MASA MILENIAL - E Zaenal Arifin (Pujangga: Jurnal Bahasa dan Sastra, 2018)
ABSTRAKKonsep guru adalah status fungsional seseorang, sedangkan orang yang membelajarkan anak didik disebut pembelajar. Konsep siswa juga merupakan status fungsional peserta didik, sedangkan orang yang sedang belajar disebut pemelajar. Kata pelajaran artinya (1) ‘yang dipelajari atau yang diajarkan’ atau (2) ‘latihan’. Daftar yang biasanya ditempelkan di dinding kelas disebut daftar pelajaran, dan bukan daftar pengajaran.  Frasa tahun ajaran  artinya ‘tingkatan masa siswa belajar dan bukan tahun pelajaran. Guru bahasa dan sastra pada masa milenial hendaklah memiliki sifat a) ulet, b) sabar, c) inovatif, d) produktif, e) periang, dan f) idola  siswa. Guru pada Era Edukasi 4.0 memiliki beberapa profil, seperti 1) mau belajar sepanjang hayat, 2) sukses dan profesional, 3) memiliki kualitas pribadi yang baik, dan 4) pandai dalam pengelolaan kelas.Kata Kunci: pembelajar, pemelajar, guru, siswa, era edukasi 4.0  ABSTRACTThe concept of the teacher is the status of a person, while the person who teaches learners is called an instructors. The concept of students is also a status, while people who are studying are called learners. The word lesson means (1) "learned or taught" or (2) "practice". Lists that are usually posted on a classroom wall are called lesson lists, and not a list of teachings. The school year phrase means ‘the level of student learning time and not the school year. Language and literature teachers in the millennial era should have the characteristics of a) tenacious, b) patient, c) innovative, d) productive, e) cheerful, and f) student idols. Teachers in the Education 4.0 era have several profiles, such as 1) willing to learn throughout life, 2) success and professionalism, 3) having good personal qualities, and 4) teachers who are good at classroom management.Keywords: instructor, learner, teacher, student, the education 4.0 era